THE IMPACT OF INDONESIA CAPITAL RELOCATION TO KALIMANTAN PEATLAND RESTORATION - Theresia; Ricky Martin Sihombing; Florentina Simanungkalit (Sociae Polites, 2020)
East Kalimantan is the location designated by President Jokowi Dodo as the new capital city of Indonesia. In terms of autonomy, the reason for moving the capital city according to the government is for the sake of equitable development. Decentralization is the idea and spirit of the founders of the state, with division of territories including their powers. This is stated in the provisions of Article 18 of the 1945 Constitution which encourage the implementation of regional autonomy in a broad and concrete manner, with the hope that disadvantaged areas can develop themselves and align themselves with other regions in order to advance welfare. The relocation of the new capital city will create new problems in this country, not only peat problems, but will result in ecological disasters. It is hoped that the relocation of the capital city will really be studied and evaluated because it will seriously threaten the sustainability of peatlands in East Kalimantan, where 0.3 million hectares are peatlands. The role of local government is very important because in its implementation in realizing good environmental governance, the ability of local governments to protect and manage the environment is needed. This study uses a qualitative research approach which is a scientific method used and carried out by a group of researchers in the field of social sciences, including education. Keywords: Peatland Restoration, Political Ecology, Respons to Indonesia Capital Relocation, Decentralization, Regional Autonomy